Pengaruh lama perendaman dan aplikasi agens hayati Bacillus subtilis dan Pseudomanas fluorescens terhadap pertumbuhan benih tanaman sawi hijau (Brassica juncea L.) - Sumardi Noor; Dewi Melani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: The use of non-pathogenic bacteria explored from plant roots (rhizobacteria) belonging to the Plant Growth Promoting Rhizobacteria (PGPR) group. This study aims to utilize Plant Growth Promoting Rhizobacteria (PGPR) Bacillus subtilis and Pseudomonas fluorescens on the growth of Caisim mustard seeds (Brassica juncea L.). Methods: This study used a completely randomized design (CRD). The first factor is the type of bacteria, B0 = control, B1 = Bacillus substilis, B2 = Pseudomonas fluorescens, and B3 = Bacillus substilis and Pseudomonas fluorescens. The second factor is the immersion time, T1 = 10 minutes, T2 = 20 minutes, and T3 = 30 minutes. From these two factors, 12 treatment combinations were obtained and each treatment combination was 6 (six) times. Results: The results showed that the B3T3 treatment combination of Bacillus substilis and Pseudomonas fluorescens biological agents treatment with 30 minutes resulted the highest plant height (4.20 ± 0.036), number of leaves (3.83 ± 0.408), and wet weight (0.130 ± 0.009) and the highest seed vigor was 92% compared to the other treatments. Conclusion: The growth of mustard greens (Brassica juncea L.) was significantly affected by the application of the biological agents Bacillus subtilis and Pseudomonas fluorescens as well as the duration of soaking the seeds in these biological agents.